DINAMIKA KEPEMIMPINAN DALAM PENGAMBILAN KEPUTUSAN KOLABORATIF PADA PROSES MUSRENBANG DI BAPPEDA KOTA PADANG - Tri Oktary, Rifha; Syamsir; Laila Rani, Nabila; Hasanah, Miftahul; Handayani, Zara; Alif Zeliq, Muhammad; Syaputra, Ifandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore leadership patterns in the Development Planning Deliberation (Musrenbang) at the Padang City Regional Development Planning Agency (Bappeda) and its impact on collaborative decision-making. Musrenbang is a collaborative forum involving the government, the Regional People's Representative Council (DPRD), regional officials, and the community in determining development priorities. The method used in this study is a descriptive qualitative approach through interviews with relevant parties. The focus of this research includes leadership patterns, decision-making stages, leaders' contributions in encouraging engagement, negotiation dynamics, supporting and inhibiting factors, and their influence on the quality of decisions made. The results of this study are expected to demonstrate that participatory, communicative, and adaptive leadership can improve decision quality and produce development plans that are more responsive to community desires.